Coupling Between Alfvén Wave and Kelvin–Helmholtz Waves in the Low Latitude Boundary Layer - Kim, E.-H.; Johnson, J. R.; Nykyri, K. (Frontiers in Astronomy and Space Sciences, 2022)
The Kelvin-Helmholtz (KH) instability of magnetohydrodynamic surface waves at the low latitude boundary layer is examined using a time-dependent wave code, including the effects of sheared flow. When the magnetosheath flows are perpendicular to the ambient magnetic field direction, unstable KH waves that propagate obliquely to the sheared flow direction occur at the sheared flow surface when the Alfven Mach number is higher than an instability threshold. Including a shear transition layer between the magnetosphere and magnetosheath leads to secondary KH waves (driven by the sheared flow) that are coupled to the resonant surface Alfven wave. There are remarkable differences between the primary and the secondary KH waves including wave frequency, the growth rate, and the ratio between transverse and the compressional component. The secondary KH wave energy is concentrated near the shear Alfven wave frequency at the magnetosheath with a lower frequency than the primary KH waves. Although the growth rate of the secondary KH waves is lower than the primary KH waves, the threshold condition is lower, so it is expected that these types of waves will dominate at lower Mach number. Because the transverse component of the secondary KH waves is stronger than the primary KH waves, more efficient wave energy transfer from the boundary layer to the inner magnetosphere is expected.